The osteomyelitis study in the New Zealand white rabbit (NZWR) model: An approach to treatment - Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli (2018)
INTRODUCTION: Treatment of osteomyelitis is still a major challenge in orthopedics. Study of osteomyelitis and infection requires the use of suitable animal. New Zealand white rabbit (NZWR) (Oryctologus cuniculus) is an acceptable experimental model. It is used for local delivery of antibiotics in osteomyelitis treatment as it mimic the disease process in human. The objectives of this study are to create osteomyelitis in rabbit femur and to analyze the treatment given via biomaterials impregnated with gentamicin beads. MATERIALS & METHODS: Osteomyelitis is induced by inoculation of Staphylococcus aureus ATCC 25923 into the drilled distal femur of NZWR. The weights of the rabbits were weight between 2.5 and 4.2 kg., all aged above 6 months old. Thirty-four (34) NZWR were used during the study. They were divided into 2 groups (hydroxyapatite(HA) and calcium sulphate (Ca2SO4) with four subgroups with 3, 6, 12 and 26 weeks. There are two surgeries for each NZWR, first to induced infection and second surgery is to undergo surgical debridement and biomaterial impregnated antibiotics implantation. The response of the treatments (biomaterials impregnated with gentamicin) against the infection were evaluated through gross presentations, radiograph, micro CT, microbiological and histological results. SPSS was used to evaluate the results. RESULTS: Osteomyelitic changes noted in all rabbit after inoculation of bacteria. The rabbits’ weights reduced after 3 weeks of bacteria inoculation. After the treatment with biomaterial impregnated antibiotics, they showed significant increase in weights. Its showed significance weight difference (p<0.05) at week 12 and 26 in